Comprehensive long‐term safety of adalimumab from 18 clinical trials in adult patients with moderate‐to‐severe plaque psoriasis3. (10th October 2018) - Leonardi, C.; Papp, K.; Strober, B.; Thaçi, D.; Warren, R.B.; Tyring, S.; Arikan, D.; Karunaratne, M.; Valdecantos, W.C.
Summary: Background: Adalimumab (Humira ®, AbbVie Inc., North Chicago, IL, U.S.A.) is a fully human monoclonal antibody specific for tumour necrosis factor‐α that is approved to treat adults with moderate‐to‐severe chronic plaque psoriasis. Objectives: To assess long‐term safety for patients with psoriasis receiving adalimumab in clinical studies. Methods: Adalimumab safety data from adults with psoriasis who received at least one adalimumab dose in 18 clinical trials were evaluated. Adalimumab was delivered subcutaneously in all treatment regimens. Treatment‐emergent adverse events (AEs) were collected from the first dose to 70 days after the last dose or cut‐off date (31 December 2015). AE incidence rates were expressed as events per 100 patient‐years (E/100 PYs) of adalimumab exposure. Standardized incidence ratios (SIRs) for malignancies and standardized mortality ratios (SMRs) were calculated. Results: Cumulative exposure was 5429·7 PYs in 3727 patients. Overall, there were 16 536 AEs (304·6 E/100 PYs). The most common AEs were nasopharyngitis, upper respiratory infection and headache (23·7, 12·9 and 7·9 E/100 PYs, respectively). Incidence rates for serious infections, tuberculosis and opportunistic infections were 1·8, 0·3 and 0·02 E/100 PYs, respectively. Incidence of malignancy excluding nonmelanoma skin cancer (NMSC) was 0·8 E/100 PYs [SIR 0·86, 95% confidence interval (CI) 0·58–1·23]. Incidences of NMSC and melanoma were 0·6 and 0·2 E/100 PYs, respectively. The SIR was 1·55 (95% CI 1·10–2·13) for NMSC and 3·04 (95% CI 1·11–6·62) for melanoma. The SMR was 0·34 (95% CI 0·16–0·65). Conclusions: AE rates remained stable in this analysis of patients with psoriasis receiving adalimumab; no new safety signals were identified compared with earlier analyses. Abstract : What's already known about this topic? The long‐term safety of adalimumab has been established in > 23 000 patients in clinical trials across multiple indications. A previous comprehensive safety analysis of long‐term adalimumab clinical data for the treatment of psoriasis from 13 clinical trials demonstrated a favourable safety profile for adalimumab in psoriasis. What does this study add? Five additional adalimumab clinical trials in psoriasis have been completed since the November 2009 analysis. This comprehensive long‐term integrated analysis of adalimumab safety in 3727 patients with psoriasis enrolled in 18 clinical studies found no new safety signals and was comparable with the previous safety report. The adverse event rates remained stable and consistent with currently approved labelled indications over increased adalimumab exposure time. Linked Comment:  Ryan. Br J Dermatol 2019;180 :14–15 . Plain language summary available online Respond to this article